Ownership Concentration and Asset Risk-Return Profiles : A Quantitative Study of Systematic and Idiosyncratic Risks - Nainggolan, Rexon; Montebon, Clarijun Quimada (Universitas Muhammadiyah Surakarta, 2026)
This study investigates the complex relationships between ownership concentration and asset risk-return profiles. Using a quantitative methodology, the research employs a market model framework and Ordinary Least Squares (OLS) regression to analyze data from publicly listed companies. The analysis quantifies how shareholding distribution influences key financial metrics, including expected excess returns (alpha), systematic risk sensitivity (beta), and stock volatility. The novelty of this research lies in its distinction from previous econometric studies by integrating ownership structure analysis directly into foundational market model metrics, providing a new lens through which to view the interplay between governance and firms’ risk-returns profiles. The study findings demonstrates that ownership concentration significantly shapes asset risk-return profiles. The result reveals a positive correlation between con-centrated ownership and superior risk-adjusted performance (Alpha), driven by reduced agency costs and strategic oversight. While the impact on systematic risk (Beta) is often secondary to macroeconomic factors, the data indicates a stabilizing effect where higher concentration reduces idiosyncratic volatility. Furthermore, the study identifies a low-beta anomaly, suggesting that firms generating higher alpha do not necessarily carry increased market risk. These insights contribute to the discourse on modern financial markets by highlighting internal governance as a critical mediator of asset behavior, offering valuable guidance for investment strategies and corporate governance decisions.